Clinical biomarkers to predict preoperative lymph node metastasis in endometrial cancer - Şahin, H. Öztürk; Yılmaz, Alpay; Sıddıkoğlu, Duygu (Journal of Surgery and Medicine, 2021)
Background/Aim: Although the evaluation of preoperative lymph node metastasis is very important for the appropriate approach of the surgeon, it cannot be determined precisely. We aimed to investigate preoperative systemic inflammatory markers and the value of CA 125 in the prediction of lymph node metastasis (LNM) in epithelial endometrial carcinoma. Methods: In our retrospective cohort study, 327 patients were pathologically diagnosed with epithelial endometrial carcinoma and underwent surgical staging including lymphadenectomy. We investigated preoperative serum CA 125, neutrophil/lymphocyte (NLR) and thrombocyte/lymphocyte (PLR) values and their relationship with LNM. ROC analysis was performed to these variables for prediction of LNM. Results: There was a significant difference between histological type (P=0.021), myometrial invasion (P<0.001), lymphovascular space invasion (LVSI) (P<0.001), and peritoneal cytology (P=0.001) in those with and without LNM. Among the NLR, PLR and CA 125 values, only CA 125 was significantly higher in the LN positive group compared to the LN negative group (P=0.516, P=0.408 and P=0.001, respectively). The optimal CA 125 cut-off value in the preoperative diagnosis of LNM was ≥39.0 U/ml. The diagnostic sensitivity, specificity, PPV, NPV, and accuracy values of CA 125 were 77%, 82%, 48%, 94%, and 81%, respectively. Conclusion: While preoperative CA 125 value was a significant predictor for LNM in epithelial endometrial cancers, we did not detect this relationship in NLR, PLR and systemic inflammatory markers.